Evaluation Model for Supply Chain Agility in a Fuel Oil Supply Company - Seker, Sukran (SPRINGER INTERNATIONAL PUBLISHING AG, 2022)
Agile supply chain must be able to respond quickly to fluctuations, delays and unforeseen actions to meet customer expectations, having competitive advantage and develop their business activities. To achieve this, managers must optimize and improve logistics operations efficiently, and meet demand easily by applying the latest technology and automation. As a result, providing data in real-time to meet demand on time is important to obtain competitive advantage in a competitive environment. In this study, the most important agility factors are weighted and prioritized considering Fuel Oil Supply Company. In the evaluation process Interval-Valued Pythagorean Fuzzy (IVPF)-Analytic Hierarchy Process (AHP) is used. As a result, Flexibility to changes is obtained as the most important agile factor in supply chain for Fuel Oil Supply Company.
Keywords: Agility; Supply chain; Uncertainty; MCDM; LOGISTICS; Computer Science